A Hospital-Based Study on the Prevalence of Keratoconus in First-Degree Relatives of Patients with Keratoconus in Central China. (26th May 2022) - Wang, Yawen; Xu, Liyan; Wang, Shaopei; Yang, Kaili; Gu, Yuwei; Fan, Qi; Wang, Qing; Zhu, Meng; Guo, Kai; Pang, Chenjiu; Ren, Shengwei; Zhao, Dongqing
Abstract : Purpose . The present study investigated the prevalence of keratoconus (KC) among first-degree relatives of KC patients in Central China. Methods . From July 2018 to March 2022, 661 first-degree relatives of 384 KC patients were included in the present study. Corneal tomography, uncorrected distance visual acuity, manifest refraction with corrected distance visual acuity, intraocular pressure, slit-lamp microscopy, and fundus examination were performed. The diagnosis of KC was based on the Belin/Ambrosio enhanced ectasia total deviation value (BAD-D value) on the Pentacam® system (Oculus GmbH). BAD-D value <1.6 was diagnosed as healthy, 1.6≤ BAD-D value <2.6 was diagnosed as suspected KC, and BAD-D value ≥2.6 was diagnosed as KC. Results . The present study included 337 (50.98%) female and 324 (49.02%) male subjects. The prevalence of KC and suspected KC in first-degree relatives was 8.77% ( n = 58) and 29.05% ( n = 192), respectively. The prevalence of KC was 9.70% among parents and 7.23% among siblings. Conclusions . The higher prevalence of KC among first-degree relatives of patients with KC suggests that first-degree relatives of KC are at high risk of developing KC.